ISOLATION, PRODUCTION AND CHARACTERIZATION OF EXTRACELLULAR PECTINASE FROM Aspergillus niger K3 - ROHIT K C; SUDIPTA K M; PURUSHOTHAM B; KUMARA SWAMY M (International Journal of Pharma and Bio Sciences, 2013)
A pectinase producing fungus was isolated from compost soil. Morphological characteristics, microscopic observations and molecular characterization based on internal transcribed spacer (ITS) sequences led to its identification as Aspergillus niger (GenBank Accession Number: JX556221) and it was designated as Aspergillus niger strain K3. In the present study, the culture condition of the media was found to have a marked effect on pectinase production. The optimum pH and temperature for maximum pectinase activity was 8.0 (70U/ml) and 450C (90U/ml), respectively. The best carbon sources that induce pectinase production was found to be fructose (40U/ml) followed by maltose (38U/ml). Among the nitrogen sources, ammonium nitrate (80U/ml) produced maximum pectinase followed by peptone (72U/ml).